Study guide to Biblical eldership twelve lessons for mentoring men for eldership - Strauch, Alexander, 1944- (Littleton, CO Lewis and Roth, 1996)
Includes bibliographical references and index.
Brethren writer. Text is held at 262.05/STR.
Keywords: Elders (church officers) -- biblical teaching; Christian leadership -- biblical teaching; Bible -- criticism interpretation, etc